Peran Audit Siklus Aset Tetap Dalam Meningkatkan Transparansi Dan Akuntabilitas Pengelolaan Entitas Bisnis Modern - Nurfaika, Nurfaika; Nurfauziah, Nurfauziah; Mashyuri, Mashyuri (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study examines the role of the fixed asset cycle audit in enhancing transparency and accountability in the management of modern business entities. Fixed assets represent a significant portion of organizational resources and require responsible management to ensure reliable financial reporting and sound corporate governance. The research adopts a qualitative approach through a structured literature review of auditing textbooks, empirical studies, and prior research related to fixed asset auditing, internal control, and managerial accountability. The findings indicate that the fixed asset cycle audit plays a critical role in improving the quality of asset disclosure, strengthening managerial responsibility, and supporting effective internal control systems. Audit procedures focused on existence, valuation, and compliance contribute to more transparent reporting and reduce the risk of misstatement and asset mismanagement. Furthermore, the integration of fixed asset audits with risk-based audit approaches enhances the organization’s ability to mitigate operational and financial risks. The study highlights that a well-implemented fixed asset audit supports stakeholder trust and reinforces sustainable business practices. These findings provide valuable insights for auditors, management, and policymakers in strengthening governance frameworks related to asset management.